Tuning ionic liquids for natural gas dehydration using COSMO-RS methodology - Gonfa, G. (Elsevier B.V., 2015)
The quantum chemical COSMO-RS (Conductor like Screening Model for Real Solvents) methodology was applied to evaluate the ability ionic liquids as alternative solvents for dehydration of natural gas. First, a general evaluation of COSMO-RS model to predict activity coefficients at infinite dilution of water in ionic liquids were performed by comparing the computed results with a set of experimentally measured activity coefficient of water in different ionic liquids over various temperatures. The mean prediction error (MPE) and linear correlation coefficient (R2) between the experimental and predicted activity coefficients are 29.9 and 0.968, respectively. Then, a detailed analysis of water and ionic liquids behaviors and the effects of possible structural variation of ionic liquids on the water-ionic liquids interactions were performed using the sigma-profile and sigma-potential generated by COSAMO-RS model. For which, a total of 31 cations and 43 anions resulting in 1333 possible combinations were screened via COSMO-RS model by calculating the activity coefficient of water in these ionic liquids at infinite dilution over temperature range of (298.15â368.15) K. It was found that ionic liquids the contain cations with longer alkyl chain show less affinity for water molecules. Moreover, ionic liquids with fluorinated and cyano anions shows lower affinity and selectivity for water molecules. However, ionic liquids containing carboxylate and amino acid based anions and cations with shorter alkyl side chain have strong affinity and more selectivity for water molecules. Â© 2015 Elsevier B.V.